Analysis Of Convict’s Rights In Judicial Review Of Narcotics Criminal Case - . Yulianto (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
Implementation Act in people's daily life has great significance, because the purpose of the law lies precisely in the implementation itself. Criminal act law that is laid down by courts of law often causes problems, especially if the verdict contains elements of a mistake. But in the Act, it still provides remedies for the convict to hold self-defense. Legal remedies are some rules that intended to defend the convicted person or his heirs. The last legal remedy provided by law is Judicial Review .The problem of this thesis is how the legal power of the Supreme Court of Cassation in a criminal case, what factors that make the defendant doing Reconsideration of narcotics criminal cases, and how the rights of the accused in Narcotics  Reconsideration. Discussion of criminal case in this study is known that the force of law by the Supreme Court of Cassation decision on the criminal case is legally binding, under Article 263 Paragraph (1) Code of Criminal Procedure a.k.a KUHAP), which is: Against the court decision which has obtained permanent legal force, unless acquittal or separated from all charges, convicts or their heirs may file a request for judicial review to the Supreme Court. Factors underlying the defendant does Reconsideration Criminal Case under Article 263 Paragraph narcotic (2) Criminal Procedure Code, there are three reasons, new evidence (Novum), difference verdict, judge's mistake. And the rights of defendants in legal action,  Reconsideration based on the decision of the Constitutional Court that removes Article 268 Paragraph (3) Criminal Procedure Code the accused has the right to take legal actions repeatedly Reconsideration more than once. Based on the results of this study,it is suggested that the Constitutional Court gives clarity toward Article 268 Paragraph (3) Criminal Procedure Code(KUHAP)that has been removed with the aim of creating legal certainty and justice for the accused or the victims of crime.